The plasmid-encoded lactose operon plays a vital role in the acid production rate of Lacticaseibacillus casei during milk beverage fermentation - Li, Xiaoxia; Zhai, Zhengyuan; Hao, Yanling; Zhang, Ming; Hou, Caiyun; He, Jingjing; Shi, Shaoqi; Zhao, Zhi; Sang, Yue; Ren, Fazheng; Wang, Ran (Frontiers in Microbiology, 2022)
Lacticaseibacillus casei is used extensively in the fermented milk-beverage industry as a starter culture. Acid production capacity during fermentation is the main criterion for evaluating starters although it is strain-dependent. In this study, the acid production rates of 114 L. casei strains were determined and then classified into high acid (HC), medium acid (MC) and low acid (LC) groups. Comparative genomics analysis found that the lac operon genes encoding the phosphoenolpyruvate-lactose phosphotransferase system (PTSLac) were located on plasmids in the HC strains, however, it is notable that the corresponding operons were located on the chromosome in LC strains. Real-time PCR analysis showed that the copy numbers of lac operon genes in HC strains were between 3.1 and 9.3. To investigate the relationship between copy number and acid production rate, the lac operon cluster of the HC group was constitutively expressed in LC strains. The resulting copy numbers of lac operon genes were between 15.8 and 18.1; phospho-β-galactosidase activity increased by 1.68-1.99-fold; and the acid production rates increased by 1.24-1.40-fold, which enhanced the utilization rate of lactose from 17.5% to 42.6% in the recombinant strains. The markedly increased expression of lac operon genes increased lactose catabolism and thereby increased the acid production rate of L. casei.